2012
DOI: 10.1174/021093912803758228
|View full text |Cite
|
Sign up to set email alerts
|

Validación del Cuestionario de Conflicto Interpersonal en el Trabajo (CIT) en empleados españoles

Abstract: interpersonales en el trabajo (CIT) en sus dos dimensiones (conflicto de tareas vs. conflicto de relaciones). Para ello, realizamos dos tipos de análisis con una muestra de 209 trabajadores provenientes de diferentes organizaciones españolas. El objetivo del primero fue la confirmación de la estructura factorial del cuestionario (AFC) y la demostración de su fiabilidad. El objetivo del segundo fue demostrar la validez predictiva de ambas dimensiones. La versión en español de conflictos interpersonales en el tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
(47 reference statements)
1
6
0
5
Order By: Relevance
“…Consequently, our results represent a contribution to intragroup conflict literature as no previous versions and validations of the ICS have both validated the updated conflict typology (task-, relationship- and process-oriented conflicts with items free of emotional connotations) and demonstrated its multi-level applicability (Benítez et al , 2012; Lehmann-Willenbrock et al , 2011; Pearson et al , 2002). Thus, our findings show that theoretical individual-level structure can be applied to a nested data structure.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Consequently, our results represent a contribution to intragroup conflict literature as no previous versions and validations of the ICS have both validated the updated conflict typology (task-, relationship- and process-oriented conflicts with items free of emotional connotations) and demonstrated its multi-level applicability (Benítez et al , 2012; Lehmann-Willenbrock et al , 2011; Pearson et al , 2002). Thus, our findings show that theoretical individual-level structure can be applied to a nested data structure.…”
Section: Discussionsupporting
confidence: 55%
“…First, our results revealed that a bi-dimensional model of conflict types at work (i.e. task-oriented conflict vs relationship-oriented conflict) could apply to perceptions of conflict at the individual level (Benítez et al , 2012; González-Navarro et al , 2017; Pearson et al , 2002). However, adopting an individual-level approach neglects the nested nature of the phenomena and brings to the wrong assumption of independence of the measures (i.e.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Interpersonal Conflicts. This variable was measured through the interpersonal conflict at work questionnaire (CIT), in its Spanish version [46], that comprised both task-oriented conflicts (e.g., "How often do people in your team disagree about opinions regarding the work being done?") and relationship-oriented conflicts (e.g., "How much plotting takes place behind the scenes?").…”
Section: Instruments and Measuresmentioning
confidence: 99%
“…En el manejo de los conflictos laborales es menester promover iniciativas basadas en el consenso que proporcionen servicios de conciliación o mediación, con el fin de que estas diferencias no se transformen en conflictos de mayor magnitud. Cuando existe un ambiente laboral conflictivo, las relaciones en el trabajo se transforman en generadores de estrés que afectan el entorno psicosocial del trabajador y alteran la productividad, la eficacia y la eficiencia de la organización (10).…”
Section: Introductionunclassified